BUILDING EVOLUTION OF AN EVALUATION INSTRUMENT OF THE PHYSICAL ACTIVITY LEVEL FOR OLD PEOPLE - CURITIBATIVA (Fiep Bulletin - online, 2013)
INTRODUCTION: It is practically an agreement among health professionals that physical activity is a determining factor in the progression of ageing process, being associated with the improvement of health indicators and quality of life. The measurement of the physical activity level is necessary in different interventions for old people. In contrast, the instruments used in this attempt do not seem to be qualified because they are in questionnaire form. Although, the level of physical activity is an indicator will quantify and determine the orientations to exercise practice as the actions of the Programs developed to this population. OBJECT: Introduce the building pathways of the instrument to evaluate the physical activity level in old people from Curitibativa Program, the discussions based on researches results with different instruments, the difficulties related by the teachers of the elderly groups, the proposed changes along eight years of its evolution and the final result: the introduction of a new instrument. RESULTS AND CONCLUSION: Considering the evolution in the creation of this instrument, it is believed that it fits the needs of Curitibativa Program teachers and other groups that are studying the universe of active ageing. As any and all research instrument, are necessary more studies of its application in different populations and, if necessary, more studies to its correspondence to the proposed issue.
Keywords: Evaluate instrument; physical activity; aging